Vício por “insegurança ambiental” em produtos programados para obsolescência - Costa, Talitha Giovanna Maranhão da (2022)
This master's thesis deals with the normative framework of the conduct of manufacturing and putting into circulation products with intentionally reduced useful life, a phenomenon known as "programmed obsolescence", in order to analyze the legal repercussions that such practice may entail, having as interpretative reference the called “helical consumption relationship paradigm”. Based on this theoretical archetype, Brazilian legislation, jurisprudence and doctrine will be studied, as well as, in a subsidiary way, the related international standards, in order to produce a proposal for remodeling the institute of "defect by insecurity", namely in the so-called "fact or product defect", related to consumer accidents and disciplined by arts. 8 to 17 of the Consumer Protection Code, with the aim of covering a new category, herein called "defect due to environmental insecurity " in products with an intentionally reduced useful life from manufacture, taking the aforementioned theory as pressuposition. For this reasoning to be developed, methodological inferences of predominantly deductive type will be used, proceeding to the interpretive extraction from general premises applicable to the proposed hypotheses, by the theoretical biases of programmed obsolescence, of product quality defects due to insecurity – quality theory – in comparison with the aforementioned theory of helical consumption, until reaching not only consumer patrimonial protection measures but also increased protection of the environment, from which it is possible to claim compensation for environmental damage caused by such practice (arts. 12 and 14 of the CDC).